Tatahan dan Sunggingan Wayang Golek Menak Yogyakarta - Dewanto Sukistono; Timbul Haryono; R.M. Soedarsono; Soetarno - (Institut Seni Indonesia Yogyakarta, 2009)
The Sculpture and Painting of Yogyakarta Wooden Puppet. The wayang golek Menak is one of the threedimensionalpuppet performance in Indonesia. The ‘Menak’ word indicate that the story was taken from the ‘SeratMenak’, that’s different version with wayang golek Purwa wich taken from ‘Mahabarata’ or ‘Ramayana’ story, thatwas popular in West Jawa. In Yogyakarta, wayang golek Menak was popularized by Ki Widiprayitna about 1950.Based on differences in the source story, then of course there are also differences in the form of puppets, included inthe carving and coloration techniques, in Javanesee language is called ‘tatahan’ and ‘sunggingan’. This article intendsto reveal the concept of carving and coloration, especially the style of Ki Widiprayitna.